الوعي الحداثي في نقد "عبد الملك مرتاض" بين الأصالة و المنجز الغربي - الأطرش, شيماء; جاب الله, أحمد (جامعة الوادي - university of Eloued, 2021)
يعتبر "عبد الملك مرتاض" من النقاد البارزين في طرح قضية الحداثة وعلاقتها بالتراث، أي الدعوة لمسايرة الراهن دون الابتعاد عن الماضي بما يزخر به من ثراء فكري، وحمولة معرفية. وذلك من خلال التنظير لأهمية حضور التراث العربي في المشهد النقدي العربي. كما أكد على أهمية الانفتاح على الحداثة الغربية والتعامل معها بنضج ووعي، مع ضرورة الحفاظ على الانتماء العربي التراثي أي–التفاعل الإيجابي بين المنجزيين-. وقد مكنته هذه الرؤية من ولوج الساحة النقدية العربية، وترك بصمته و هويته النقدية فيها. : Abdul-Malik Murtadh is considered as one of the prominent critics in raising the issue of modernity and its relationship to heritage, which means the call to pursue the present without neglecting the past with its intellectual richness and knowledge load. This is through theorizing regarding the significance of the Arab heritage in the Arab critical scene. In addition, he emphasized the importance of being open to the western modernity while being mature and aware and preserving the Arab heritage belonging, that is, the positive interaction among the achievers. This allowed him to reach the Arab critical arena and to draw his own critical imprint and identity
مقال
Keywords: الحداثة